CORPORATE GOVERNANCE REFORM: FOSTERING ETHICAL LEADERSHIP FOR SUSTAINABLE DEVELOPMENT - Chhuttani, Pankaj (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Corporate governance reform is crucial for fostering ethical leadership within corporations and advancing sustainable development goals. This paper explores key trends and strategies in corporate governance aimed at promoting ethical behaviour and responsible business practices. Stakeholder-oriented governance models emphasize the inclusion of diverse stakeholders in decision-making processes, enhancing accountability and trust. Board diversity initiatives seek to bring varied perspectives to the table, enabling better risk management and decision-making related to sustainability challenges. Moreover, linking executive compensation to sustainability performance metrics incentivizes ethical conduct and aligns financial incentives with long-term sustainability goals. By embracing these governance reforms, corporations can enhance their commitment to ethical leadership and contribute to sustainable development objectives. This paper underscores the transformative potential of corporate governance in driving positive social and environmental impact, urging further research and implementation of governance reforms to address pressing global challenges.